2021
DOI: 10.1177/00207209211002077
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Research and implementation of mechanical virtual experiment teaching platform

Abstract: Virtual experiment teaching is an important part of higher education institutions and research institutions. It plays an important role in helping students develop basic experimental research capabilities and innovative experimental research concepts. Mechanical majors focus on the cultivation of students' practical hands-on ability, but the traditional mechanical experimental equipment update iteration is slower, the experimental cost is higher, and there are potential safety hazards. In order to solve the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The comparison results of this paper's model with other methods for different user sequence lengths K are shown in Figures 5 and 6. The range of values taken for different user sequence lengths K is [1,5,10,15,20,25,30,35,40,45,507]. The results of the HR vs. NDCG comparison for the first-year students' Civics course dataset are shown in Figure 5.…”
Section: Perceptron Model Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The comparison results of this paper's model with other methods for different user sequence lengths K are shown in Figures 5 and 6. The range of values taken for different user sequence lengths K is [1,5,10,15,20,25,30,35,40,45,507]. The results of the HR vs. NDCG comparison for the first-year students' Civics course dataset are shown in Figure 5.…”
Section: Perceptron Model Performancementioning
confidence: 99%
“…To focus on cultivating students' practical ability for the characteristics of professional disciplines. Huo, J et al analyzed the development of virtual experiments, adopted B/S architecture, Bootstrap framework and Hibernate technology, utilizing the virtual reality technology and augmented reality technology design in the Unity3D environment, and successfully designed and realized a mechanical virtual experimental teaching platform [10]. Luo, Y. proposed a real-time monitoring system based on artificial intelligence technology for Civics classes in colleges and universities and constructed model functional modules according to the actual needs of Civics class monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from studies have shown that such teaching approach is of practical significance to improve the computer distance teaching mode and promote the smooth development of computer distance teaching. Huo et al [5] considered virtual experiment teaching to be beneficial to the cultivation of students' practical ability in mechanical majors. The author designed and implemented a mechanical virtual experiment teaching platform by using virtual reality technology and augmented reality technology in a Unity 3D environment.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Information fusion technology will play an increasingly important role in college vocal music teaching [13][14][15]. With the continuous progress of technology and the updating of teaching concepts, more innovative teaching methods and tools will be developed to provide more diversified and personalized support for vocal music teaching [16][17][18].…”
Section: Introductionmentioning
confidence: 99%